INVESTIGATION OF THE RELATIONSHIP BETWEEN ISLAMIC MARKETING AND ISLAMIC FINANCE OF CUSTOMERS OF PARTICIPATION BANKS (Third Sector Social Economic Review, 2019)
The purpose of this study is; The aim of this course is to reveal the relationship between Islamic finance and Islamic marketing understanding of corporate clients of participation banks. The universe of the research consists of construction companies operating in Duzce. In this study, quantitative research method was used and the data were obtained by using face to face survey technique. In the research, a full counting method was applied and a questionnaire was given to 200 people. Of the 200 questionnaires, 189 were completed by the participants. Of the 189 collected questionnaires, 176 were found to be suitable for analysis. SPSS software was used to analyze the data. Factor and correlation analyzes were applied to the data obtained. According to the results of factor analysis, five dimensions related to Islamic marketing concept and three dimensions related to Islamic finance have emerged. The dimensions related to Islamic marketing: Islamic product, Islamic pricing, Islamic distribution, Islamic promotion activities and human. The dimensions related to Islamic finance are: image, perceived religious sensitivities and perceived service quality. According to the results of the correlation analysis, between all the dimensions of the image and the Islamic marketing concept, the perceived service quality of the perceived religious sensibility and the Islamic product was related to the Islamic product, Islamic pricing and human relations.
Keywords: Participation Bank; Islamic Marketing; Islamic Finance; Participation Bank Customers; The Conception of Trade in Islam